Socio-demographic characteristics affecting sport tourism choices: A structural model - Nataša Slak Valek; Mike Shaw; Jakob Bednarik (Palacký University Olomouc, 2014)
Background: Effective tourism management in the field of sports tourism requires an understanding of differences in socioeconomic characteristics both within and between different market segments. Objective: In the broad tourism market demographic characteristics have been extensively analyzed for differences in destination choices, however little is known about demographic factors affecting sport tourists' decisions. Methods: A sample of Slovenian sports tourists was analyzed using data from a comprehensive survey of local and outbound tourist activity conducted by the Statistical Office of the Republic of Slovenia in 2008. After data weighting the information for 353,783 sports related trips were available for analysis. The research model adopted suggests that four socio-demographic characteristics (gender, age, level of education and income) significantly affect a tourist's choice of sports related travel either locally within Slovenia or to a foreign country. Furthermore the destination (local or foreign) has an influence on the choice of the type of accommodation selected and the tourist's total expenditure for the trip. For testing the first part of our model (the socio-demographic characteristics effects) a linear regression was used, and for the final part of the model (the selection of accommodation type and travel expenditure) t-test were applied. Results: The result shows the standardized β regression coefficients are all statistically significant at the .001 level for the tested socio-demographic characteristics and also the overall regression model was statistically significant at .001 level. Conclusions: With these results the study confirmed that all the selected socio-demographic characteristics have a significant influence on the sport-active tourist when choosing between a domestic and foreign tourism destination which in turn affect the type of accommodation chosen and the level of expenditure while travelling.